Ninho cheio, geração canguru: a permanência do filho adulto em casa segundo a perspectiva dos pais - Figueiredo, Mariana Grasel de (2008)
The purpose of this study was to comprehend and analyze how parents work through the process of their adult single children remaining in the parental home for an extended period. In contrast to past generations, there is a tendency in contemporary society for children to live for a longer period of time with their parents. In order to investigate this phenomenon, research was undertaken in the city of São Paulo, in which six couples were interviewed, being in each case parents with adult children between the ages of 27 to 35. The method used was qualitative research with the case study approach. The theoretical base employed involved systemic theory authors and researches and literature related to the subject. Through the data analysis of the interviews the categories were constructed to sistematise the subject and to correlate the research data. The knowledge developed with the data analyses demonstrated that these parents live at the same home with their adult children with little conflict. Parents describe the relationship with their adult children as a positive experience and they do not show significant preoccupations connected with the departure of the children from the parental home. The research also showed that the parental role is more in evidence than the marital role for these parents. It was verified that the professional success of the adult single children contribute for this concept observed in these parents, leading to a sense of accomplishment and success in the bringing-up of their children